PEMANFAATAN LIMBAH ORGANIK SEBAGAI SUMBER PAKAN ALTERNATIF DALAM MENINGKATAN PRODUKTIVITAS KAMBING PERANAKAN ETTAWA (PE) DI KELOMPOK TERNAK KERTA BANGKIT DESA GANGGA - Wandira, Ica Ayu; Dohi, Muhammad; Sadia, I Nyoman; Karni, Ine; Aminurrahman, Aminurrahman; Nano Septian, I Gede; Saedi, M. Ridwan; Hermansyah, Hermansyah; Amin, Muhammad (Jurnal Pepadu, 2025)
The availability of quality feed is a crucial factor in supporting the productivity of Peranakan Ettawa (PE) goats, which have high potential for both milk and meat production. The main challenges faced by farmers, particularly those in the Kerta Bangkit Livestock Group, Gangga Village, North Lombok, are the limited availability of forage during the dry season and the high cost of commercial feed. To address these challenges, a community service program was implemented, focusing on the utilization of organic waste as an alternative feed source. The program was conducted on June 25, 2025, involving 21 farmers as active participants. The activities included a preliminary survey, participatory socialization, training on semi-moist feed fermentation techniques using organic waste, and field mentoring. The training results showed an improvement in farmers’ knowledge and skills in processing organic waste into nutritionally valuable feed. Field evaluations recorded an average body weight gain of 62–85 g/head/day in PE goats after receiving fermented feed. In addition to reducing production costs, the program also contributed to environmentally friendly waste management. Overall, this community service program successfully enhanced farmers’ independence, supported the sustainability of smallholder livestock farming, and provided positive impacts on both community welfare and the environment. Keywords: Ettawa Crossbred Goats, alternative feed, organic waste, fermentation